2012
DOI: 10.1037/a0028814
|View full text |Cite
|
Sign up to set email alerts
|

Exploring emotion abilities and regulation strategies in sport organizations.

Abstract: This study aimed to contribute to a growing theoretical body of literature relating to the role of emotional intelligence abilities and emotion regulation strategies in creating optimally functioning in sport organizations. Semistructured interviews were conducted with 21 participants (athletes, coaches, administrators, national performance directors, and chief executive officers) representing 5 national sport organizations. Key emotion abilities (i.e., identifying, processing and comprehending, and managing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 56 publications
4
44
1
Order By: Relevance
“…Studies examining relationships between individuals' moods and collective team mood suggest that displays of emotions influence social interactions in team settings (Totterdell, 2000). Recent research among members of sport organizations has provided evidence that individuals attempted to manage others' emotions through the deliberate expression or suppression of their own emotions (Wagstaff et al, 2012); however, we could not locate any published research which has examined specific strategies athletes use to regulate their teammates' emotions. Thus, in the current study we sought to investigate athletes' use of interpersonal emotion regulation strategies within a team setting.…”
Section: Social Influences On Emotion and Interpersonal Emotion Regulationmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies examining relationships between individuals' moods and collective team mood suggest that displays of emotions influence social interactions in team settings (Totterdell, 2000). Recent research among members of sport organizations has provided evidence that individuals attempted to manage others' emotions through the deliberate expression or suppression of their own emotions (Wagstaff et al, 2012); however, we could not locate any published research which has examined specific strategies athletes use to regulate their teammates' emotions. Thus, in the current study we sought to investigate athletes' use of interpersonal emotion regulation strategies within a team setting.…”
Section: Social Influences On Emotion and Interpersonal Emotion Regulationmentioning
confidence: 98%
“…Wagstaff et al (2012) interviewed members of five Olympic sport organizations and reported that individuals' emotion regulation was influenced by their emotion abilities (ability to identify, process, comprehend, and manage emotions) and the organization's social norms regarding emotion expression. Emotion regulation is thought to affect intrapersonal outcomes (e.g., individuals' own behaviour, motivation, and emotions) as well as interpersonal outcomes (e.g., relationships within the organization).…”
Section: Social Influences On Emotion and Interpersonal Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…As this particular study focused on general performance director competencies, however, implications for the specific study and practice of culture change are limited. Furthermore, with other work in this field adopting a more holistic approach to organisational functioning (including examination of chief executive officers, administrators, volunteers, and committee members) [16,17] and not primarily focused on culture change delivery, it is difficult to extrapolate lessons for performance team-specific culture change processes. However, even if culture change does establish itself on the organisational sport psychology agenda, which seems likely and valuable [15], ensuing knowledge would arguably provide diluted implications for the process as it prevails in elite team performance departments.…”
Section: Introductionmentioning
confidence: 99%
“…It is for the reader to decide the extent to which the content overlaps with their 3 own experiences. In evaluating the significance of contribution of the research, one might 4 consider the theoretical (e.g., implications for conceptual understanding), heuristic (e.g., 5 stimulation of curiosity, discourse, and further exploration), and practical (e.g., utility of 6 knowledge for practitioners) significance of the findings (Wagstaff et al, 2012c). In attempt to 7 achieve a meaningful coherence, we feel that the study achieved its stated purpose, used 8 methods and representation practices that matched the domain and research paradigm, and 9 attentively interconnected extant literature with research foci, methods, and findings.…”
mentioning
confidence: 99%